2021
DOI: 10.3389/fevo.2021.666262
|View full text |Cite
|
Sign up to set email alerts
|

Testing Multi-Task Cancer Evolution: How Do We Test Ecological Hypotheses in Cancer?

Abstract: Recently several authors described a family of models, according to which different cancer types and subtypes fall within a space of selective trade-offs between archetypes that maximize the performance of different tasks: cell division, biomass and energy production, lipogenesis, immune interaction, and invasion and tissue remodeling. On this picture, inter- and intratumor heterogeneity can be explained in part as a product of these selective trade-offs in different cancers, at different stages of cancer prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…There is no agreement on how to infer tasks from functional data. For example, Plutynski points out that an analysis of life history and trade‐offs should draw on phenotypes and genotypes [ 28 ]. We chose the 10 cancer hallmarks to signify tasks important to the survival and growth of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…There is no agreement on how to infer tasks from functional data. For example, Plutynski points out that an analysis of life history and trade‐offs should draw on phenotypes and genotypes [ 28 ]. We chose the 10 cancer hallmarks to signify tasks important to the survival and growth of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, evo-eco thinking has not achieved tangible clinic success. As indicated by Korolev et al (2014), it is crucial to pursue the identified parallels further by making them quantitative, testable, and eventually useful insights for devising therapy strategies and methods (Plutynski, 2021). DNA sequencing technologies, and experiments with microbes and animal models have created unprecedented opportunities to revolutionize the eco-evolutionary studies on cancers.…”
Section: Key Concepts/hypotheses In Cancer Ecologymentioning
confidence: 99%
“…Considering many tasks may hinder defining trade-offs for several of the tumors that were included in the study (Hausser et al, 2019). Plutynski pointed out The Cancer Genome Atlas (TCGA) data, on which the study was based, might be biased toward the task that the study explains (Plutynski, 2021). In addition, an analysis of life history and trade-offs should draw on phenotypes as well as Correlation between hallmark enrichment in archetypes and in response to drug perturbations.…”
Section: Cell Linementioning
confidence: 99%